Penyembuhan Maag Dengan Metode Hipnoterapi Perspektif Ayurweda Di Rumah Sehat Tri Sakti Dukuh Nggrembyang Klaten - Dewi Ayu Wisnu Wardani (Kamaya: Jurnal Ilmu Agama, 2019)
Many methods have been found to help treat ulcers, both in medical and traditional ways. Non-pharmacological treatments that are now developing include how to treat traditional plants, reflexology, hypnotherapy and others. Fulfill the public towards medical treatment which is a condition for side effects from the use of drugs that can damage the liver and kidneys if used in the long term, people are now starting to look at methods of non-medical treatment. Among these non-medical treatments is hypnotherapy. This method was chosen because of the small side effects caused and more economical. Hypnotherapy is a form of mind therapy using hypnosis. Hypnosis is to bring someone to enter a state of relaxation in order to enter the subconscious mind, to be given suggestions. In hypnotherapy, when the client has entered the condition of relaxation / somnabulism the therapy process is only done. The importance of therapy is done in the subconscious because of the influence of the subconscious mind which is very large on human life. This is in line with the results of research that states that the subconscious mind is responsible for influencing and determining 95% to 99% of the thought activity process, so that the subconscious mind determines almost all of our decisions, actions, emotions and behavior. This research is a type of qualitative research, researchers use phenomenological theory, structural functional theory and behavioristic theory. The data collection techniques use the method of observation, literature, interviews and documentation. Furthermore, the results of this study explain that (1) the procedure for hypnotherapy is interview, induction, deepening, mind therapy and termination. The five stages in the practice of hypnotherapy must be really done so that the therapy process runs smoothly. (2) The benefits of the hypnotherapy method in healing ulcer patients are as follows: 1) Patients feel comfortable with themselves and the environment in which the patient is located, 2) Patients become more creative and innovative, 3) Patients become more attractive individuals, 4) patients will calm and confidence will arise. (3) Synergy combined between hypnotherapy methods with traditional Ayurvedic medicine turns out to be very capable of accelerating healing, because the drugs available are very good to be combined with the therapy, the efficacy is very effective for the treatment of acute ulcer disease. The herbal ingredients are instant ginger, arrowroot powder, gamat luxir jelly, bengkuang, Moringa leaf, turmeric, aloe vera, guava leaves and Curma Sapo.